In-between spaces what motivates young Filipino adults in binge-watching anime on streaming services - Guariña, Anton Miguel P.; Bautista, Roehl Niño (Quezon City College of Mass Communication Library, University of the Philippines Diliman, 2023)
This study aims to identify and explore the various factors that influence the motives and gratification-seeking behavior of audiences who engage in anime as their choice of media to binge-watch as it seeks to understand how audiences situate it as a practice within their lifestyles, The study will employ the Uses and Gratification theory as articulated by (Katz, E., Blumer, J. & Gurevitch, M., 1974) to describe how participants navigate through the practice as a gratification-seeking audience, along with their diverse motivations and the personalization of media. Additionally, it will incorporate Husserl's theory (1931) on phenomenology to investigate the lived experiences of the participants.

An interpretative phenomenological analysis was used to contextualize the participants' experiences who engage in the practice. The participants of the study were identified using a non-probabilistic purposive sampling technique to select young Filipino adults aged 18 to 25 who binge-watch anime. Semi-structured interviews will be used to gather data and thematic analysis will be used to find recurring patterns and themes derived from the data. The study aims to contribute to the knowledge of the dynamics between heavy media consumption and Japanese anime media through binge-watching.
Thesis
Includes bibliographical information (pages 93-102) and appendices (pages 103-151).
Keywords: Streaming video -- Philippines; Anime (Television programs) -- Philippines; Binge watching (Television) -- Philippines